2019
DOI: 10.1016/j.invent.2019.100286
|View full text |Cite
|
Sign up to set email alerts
|

Gamifying CBT to deliver emotional health treatment to young people on smartphones

Abstract: mHealth interventions promise the economic delivery of evidence-based mental health treatments like cognitive behavioural therapy (CBT) to populations that struggle to access health services, such as adolescents and in New Zealand, Māori and Pasifika youth. Unfortunately engagement with digital therapies is poor; modularisation and gamification have potential to increase their appeal. Gamifying CBT involves selecting suitable interventions, adapting them to a digital format while applying gamification principl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 58 publications
0
56
0
Order By: Relevance
“…The corresponding authors of all 27 studies were contacted; 21 authors replied. From these, 15 of the 21 studies confirmed they included a YPAG [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] ; the remaining 6 either did not use a YPAG (n=3) [28][29][30] or had YPAG members who were all aged over 18 years (n=3). 31,32,33 For the six studies where authors did not respond, we assumed a YPAG was used based on information provided in the paper.…”
Section: Identifying and Quantifying Ypag Reportingmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding authors of all 27 studies were contacted; 21 authors replied. From these, 15 of the 21 studies confirmed they included a YPAG [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] ; the remaining 6 either did not use a YPAG (n=3) [28][29][30] or had YPAG members who were all aged over 18 years (n=3). 31,32,33 For the six studies where authors did not respond, we assumed a YPAG was used based on information provided in the paper.…”
Section: Identifying and Quantifying Ypag Reportingmentioning
confidence: 99%
“…The identified studies that used a YPAG covered a range of topics such as cyberbullying, 14 supporting young people in their decision to join a clinical trial, 24 sexual health, 18,22,25 exploring novel mental health treatment options, 13,20 healthy eating interventions, 26 and treatment for conditions such as arthritis 15 and diabetes. 27 All but two of the studies were conducted in high income countries.…”
Section: Characterising Ypag Use In Researchmentioning
confidence: 99%
“…CBT with cognitive restructuring technique is effective against reducing online game addiction because cognitive restructuring technique is a technique that helps change irrational thinking in a more positive direction or towards irrational so that it can change someone's behavior (Christie et al, 2019;Dieris-Hirche et al, 2020;Kim, Han, Lee, & Renshaw, 2012;Kolstee et al, 2020;Muroff & Robinson, 2020;Taquet, Hautekeete, & Gorgeu, 2014). This is in line with the opinion of Aaron T. Beck (2011) that the cognitive behavior therapy approach is a counseling approach designed to solve problems experienced by the counselee by providing several techniques, one of which is cognitive restructuring.…”
Section: Resultsmentioning
confidence: 59%
“…Randomized trials suggest the promise of internet-and smartphone-based youth mental health tools [6][7][8][9][10]. However, formal clinical trial outcomes may not reflect the utility or usability of digital supports in naturalistic contexts.…”
Section: Introductionmentioning
confidence: 99%